PENGARUH VARIABEL KEUANGAN DAN VARIABEL INDUSTRI TERHADAP RETURN SAHAM SYARIAH - Hawu, Sylfie Aprilia Ajeng Handa; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the influence of return on assets, debt to equity ratio, earnings per share,industrial type, and firm size to the stock return. The samples are companies which their stocks are listed in JakartaIslamic Index consistently from 2012 to 2014. The analysis technique has been done by using multiple linearregression analysis, F test and t test. The result of the research shows that ROA has influence to the stock return sincethe regression coefficient value is 1,793 and the t test significance value is 0,038. DER has does not have anyinfluence to the stock return since the regression coefficient value is 0,100 and the t test significance value is 0,359.EPS has influence to the stock return since the regression coefficient value is -0,0002 and the t test significance value is0,008. Industrial type does not have any influence to the to the stock return since the regression coefficient value is -0,092 and the t test significance is 0,189. Firm size has does not have any influence to the to the stock return sincethe regression coefficient value is 0,063 and the t test value is 0,133.Keywords: return on assets, debt to equity ratio, earnings per share, industrial type, firm size.